2020
DOI: 10.1016/j.redox.2020.101737
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of PRDX6 induces mitochondrial dysfunction and cell cycle arrest at G2/M in HepG2 hepatocarcinoma cells

Abstract: Peroxiredoxin 6 (PRDX6) has been associated with tumor progression and cancer metastasis. Its acting on phospholipid hydroperoxides and its phospholipase-A2 activity are unique among the peroxiredoxin family and add complexity to its action mechanisms. As a first step towards the study of PRDX6 involvement in cancer, we have constructed a human hepatocarcinoma HepG2 PRDX6 - /- cell line using the CRISPR/Cas9 technique and have characterized the cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 80 publications
(101 reference statements)
4
38
0
Order By: Relevance
“…22 Additionally, Increasing number of studies have found that PRDXs affect the prognosis of patients with various types of tumors, including breast, liver, ovarian, and gastric cancers. [23][24][25][26] PRDX1, PRDX2, and PRDX6 have also been reported to be highly expressed in OSCC. [27][28][29] To date, few studies have investigated the relationship between the PRDX family and metastasis and prognosis of OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…22 Additionally, Increasing number of studies have found that PRDXs affect the prognosis of patients with various types of tumors, including breast, liver, ovarian, and gastric cancers. [23][24][25][26] PRDX1, PRDX2, and PRDX6 have also been reported to be highly expressed in OSCC. [27][28][29] To date, few studies have investigated the relationship between the PRDX family and metastasis and prognosis of OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…There had been reported that inhibition or deficiency of PRDX6 could increase the intracellular oxidative stress and cause the cell injury [ [39] , [40] , [41] ]. Increasing evidence had demonstrated that PRDX6 had a critical role in the development of human cancers [ 19 , 23 ]. High levels of PRDX6 has been found in multiple cancer cells and contributes to the proliferation of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the reported study [ 23 ], knockout of PRDX6 by CRISPR/Cas9 system had an antiproliferative effect in tumor cells. In the present study, we also screened the viable cell which had the deletion of PRDX6 by CRISPR/Cas9 system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have pointed out that mitochondrial dysfunction has been linked to cancer metastasis (156). During the process of TGF-b1 induced EMT, mitochondria will be damaged.…”
Section: Lung Cancermentioning
confidence: 99%